Music Listening Predicted Improved Life Satisfaction in University Students During Early Stages of the COVID-19 Pandemic - Krause, Amanda E.; Dimmock, James; Rebar, Amanda L.; Jackson, Ben (Frontiers in Psychology, 2021)
Quarantine and spatial distancing measures associated with COVID-19 resulted in substantial changes to individuals’ everyday lives. Prominent among these lifestyle changes was the way in which people interacted with media—including music listening. In this repeated assessment study, we assessed Australian university students’ media use (i.e., listening to music, playing video/computer games, watching TV/movies/streaming videos, and using social media) throughout early stages of the COVID-19 pandemic in Australia, and determined whether media use was related to changes in life satisfaction. Participants (N = 127) were asked to complete six online questionnaires, capturing pre- and during-pandemic experiences. The results indicated that media use varied substantially throughout the study period, and at the within-person level, life satisfaction was positively associated with music listening and negatively associated with watching TV/videos/movies. The findings highlight the potential benefits of music listening during COVID-19 and other periods of social isolation.